Tax Policy and Entrepreneurial Entry - Gentry, William M; Hubbard, R. Glenn (American Economic Review, 2000)
While recent research has emphasized the desirability of studying effects of changes in marginal tax rates on taxable income, broadly defined, there has been comparatively little analysis of effects of marginal tax rate changes on entrepreneurial entry. This margin is likely to be important both because of the likely greater elasticity of entrepreneurial decisions with respect to tax changes (relative to decisions about hours worked) and because of recent research linking entrepreneurship, mobility, and household wealth accumulation. Previous work focuses on how marginal tax rates affect work incentives, incentives to take compensation in taxable forms, and reporting incentives. In addition, both the level and the progressivity of tax rates can affect decisions about risky activities. The tax system offers insurance for taking risk since taxes depend on outcomes; however, asymmetric taxes on different outcomes, such as progressive rates, may discourage risk taking. Using the Panel Study of Income Dynamics for 1978-1993, we incorporate both of these effects of the tax system in empirical estimations of the probability that people enter self employment. While the level of the marginal tax rate does not affect entry into self employment in a consistent manner across specifications, we find robust results that